Lipid profile after switching from a TDF (tenofovir disoproxil)-containing to TAF (tenofovir alafenamide)-containing regimen in virologically suppressed people living with HIV - Łomiak, Michał; Gajek, Zofia; Stępnicki, Jan; Lembas, Agnieszka; Mikuła, Tomasz; Wiercińska-Drapało, Alicja (Journal of Medical Science, 2023)
Background. Tenofovir disoproxil fumarate (TDF) or its prodrug, tenofovir alafenamide fumarate (TAF), is currently being recommended in treatment of HIV infection. The distinct pharmacological properties of these two forms of this drug make TAF treatment less nephrotoxic and lead to a better impact on bone density. Nevertheless, a rising concern about TAF’s possible metabolic adverse effects exists. This study aimed to evaluate the effects on the lipid profile among ART (antiretroviral therapy) patients switching from a TDF-containing to a TAF-containing regimen in the first year after the switch. Methods. Demographic and clinical data of HIV-positive ART-experienced patients treated in the infectious diseases department was retrospectively collected. Lipid profile change concerning baseline BMI, age, and time of ART duration were analysed. Results. In the group of 36 patients, there was a significant increase in total cholesterol levels (+18.43mg/dl, SD=23.86mg/dl, p<0.0001) and LDL levels (+13.75mg/dl, SD=23.05mg/dl, p=0.001) in the first 12 months after switching from a TDF-containing to a TAF-containing regimen. There were no statistically significant changes in both HDL and TG levels observed. Analysis of total cholesterol and LDL levels in specific subpopulations revealed a significant increase within the first year after the switch in patients younger than 40 years old and in those whose BMI was within the normal range. Conclusions. The data suggests that switching from TDF to TAF in ART-experienced patients may be associated with worsening lipid parameters. Early detection and management of dyslipidemias among HIV-positive patients are needed.